Analysis Of Raw Material Inventory Control For Beef Concentrate Production Using The Economic Order Quantity (EOQ) Method - Ramadhanty Putri Herlambang; Iskandar Ali Alam (Cita konsultindo, 2024)
This research aims to analyze raw material inventory control at the Berkah Sejahtera cattle concentrate factory, before using the EOQ method and after using the EOQ method, analyzing the EOQ method can increase the efficiency of raw material inventory at the beef concentrate factory. The data analysis method used in this research is descriptive qualitative using the Economic Order Quantity method. The results of the research by using EOQ, the company can make optimal raw material purchases every time an order is 61,405 kg with a frequency of 17 times a year and the company can save total raw material inventory costs of IDR 17,545,259 with an efficiency of 45%. By conducting this research, it is hoped that companies will minimize their annual expenses.